FISH FAUNA OF SARDA SAGAR RESERVOIR IN PILIBHIT (U.P.) AND SOME RECOMMENDATIONS FOR DEVELOPMENT OF RESERVOIR FISHERIES - Motwani, M P; Saigal, B N (Indian Journal of Fisheries, 2011)
The effect of construction of Sarda Sagar on Chuka nadi, in the Pilibhitdistrict of Uttar Pradesh, on the ichthyo fauna of the river system is discussed.The existing fish stock in the reservoir appears to be that which got trapped bythe construction of the dam in 1957 and no natural stocking seems to have takenplace since. Some recommendations for proper stocking and the developmentof the fishery of Sarda Sagar are given